Planetary distribution of Geomagnetic Substorms and their Peculiarities in conjugate places - L. N. Yaremenko; T. A. Mozgovaya; V.G. Bahmutov (Ukrainian Antarctic Journal, 2005)
A comparison of magnetic substorms at the station Akademik Vernadsky, in Greenland, Japan and New Zealand detected seasonal dependence of the substorms amplitude  with maximum in the lokal winter regardless of a hemisphere. The differences are so great that the disappearance of substorms is observed in the opposite hemisphere in the local summer. Simultaneous appearance of substorms over the globe is observed as well as the amplitude and record form dependence on the longitude and local conditions. The latitudinal dependence of substorm amplitudes are given. Magnetic substorm characteristics obtained in the  Vernadsky station are presented. In general, according to the characteristics of the substorms, they are of the mid-latitudinal type. The events of the southern polar jet approach to Vernadsky station are considered separately. Examples of the same, opposed and disagreeing substorm current directions observed at  Vernadsky station and in North America are shown as well. The substorm origin dependence on the changes of the Bx and By components of the interplanetary magnetic field, its total value B and abrupt, variations of the solar wind velocity and pressure is marked.